1988
DOI: 10.1093/nar/16.12.5569
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally regulated telomere addition inTetrahymena thermophila

Abstract: To investigate the developmentally programmed telomere addition that accompanies chromosome fragmentation during macronuclear differentiation in Tetrahymena thermophila, five representative telomeric regions from the macronucleus were cloned and characterized in detail. The sequences adjacent to the telomeric (C4A2:T2G4) repeats on these five macronuclear ends had no significant sequence homology or shared secondary structure. Two developmentally independent examples of one macronuclear telomere had a 5 base p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…First, the healed end indicates that the Ca7 repeats are sufficient to function as a C. albicans telomere in the absence of the repetitive subtelomeric sequences that are present on native C. albicans telomeres. Evidence from telomere formation in ciliates and from other healed ends indicates that the terminal repeats of other species are also sufficient to function as telomeres (2,6,8,29,39,42,44). The second important implication of the C. albicans healed end is that it suggests that C. albicans cells have a mechanism for the de novo addition of telomere sequences to a free DNA end.…”
Section: Resultsmentioning
confidence: 99%
“…First, the healed end indicates that the Ca7 repeats are sufficient to function as a C. albicans telomere in the absence of the repetitive subtelomeric sequences that are present on native C. albicans telomeres. Evidence from telomere formation in ciliates and from other healed ends indicates that the terminal repeats of other species are also sufficient to function as telomeres (2,6,8,29,39,42,44). The second important implication of the C. albicans healed end is that it suggests that C. albicans cells have a mechanism for the de novo addition of telomere sequences to a free DNA end.…”
Section: Resultsmentioning
confidence: 99%
“…This idea is appealing because in vivo data point to a need for telomerase to bind to a specific DNA sequence to act. In Tetrahymena, sequences derived from the sites of telomere addition in macronuclear DNA do not contain C4A2 repeats, and they are not utilized by telomerase in vitro (Spangler et al 1988). This result suggests that there may be other telomerase recognition sequences proximal to the sites of telomere addition in Tetiahymena macronuclear chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Clues to some of these complex mechanisms have been obtained: in Tetrahymena, Yao et al (1990) identified chromosome breakage sequences involved in the fragmentation process. Other studies in Tetrahymena (Spangler et al, 1988;Yu and Blackburn, 1991) and also in Oxytricha (Zahler and Prescott, 1988) and Paramecium (Baroin et al, 1987;Bourgain and Katinka, 1991) are contributing to the understanding of telomerization. Finally, studies in hypotrichous ciliates have revealed the existence of 'DNA splicing', which consists in the specific elimination of short intragenic sequences (IES) during the differentiation of micro into macronuclear chromosomes (Klobutcher et al, 1984).…”
Section: Introductionmentioning
confidence: 99%